2008
DOI: 10.1007/s11270-008-9743-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Ecotoxicological Assessment of Selected Biologically Activated Sorbents for Treating Wastewater Polluted with Petroleum Products with Special Emphasis on Polycyclic Aromatic Hydrocarbons

Abstract: A chemical and ecotoxicological assessment of treatment of wastewater that had been polluted with petroleum products using only Activated Sludge (AS) and four biologically activated sorbents (BASs), consisting of activated sludge plus: coal-based activated carbon (-C1), coconut shell-based activated carbon (-C2), zeolite (-Z), and anthracite (-A) were conducted. The efficiency and robustness of the four wastewater treatment systems were evaluated by calculating the reduced total petroleum hydrocarbon (TPH) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…However, there are a few reports of the bioregeneration of GAC using actual industrial effluent. Augulyte et al (2008) studied the treatment of wastewater polluted with petroleum products using biologically activated sorbents. Algal and bacterial bioassays showed that the toxicities of effluents following treatment were reduced by more than 80% and 90%, respectively.…”
Section: Industrial Waste Watermentioning
confidence: 99%
“…However, there are a few reports of the bioregeneration of GAC using actual industrial effluent. Augulyte et al (2008) studied the treatment of wastewater polluted with petroleum products using biologically activated sorbents. Algal and bacterial bioassays showed that the toxicities of effluents following treatment were reduced by more than 80% and 90%, respectively.…”
Section: Industrial Waste Watermentioning
confidence: 99%
“…Indications of sorption capacities for organic substances in the wastewater were rapidly and conveniently obtained using red formazan adsorption method earlier described in Augulyte et al [18].…”
Section: Bac Quality Parametersmentioning
confidence: 99%
“…The assays measure the amounts of intensely red 1,3,5-triphenylformazan (TF) formed via the reduction of 2,3,5-triphenyltetrazolium chloride (which are proportional to the amounts of DHA present in the samples, and thus provide proxy indicators of bioactivity; [20]). For these tests, samples of BAC were taken from well-mixed reservoirs at the same time of day and analyzed according to the method described in Augulyte et al [18].…”
Section: Bac Quality Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The performed toxicological tests allow simultaneous determination of harmful effects of all the substances contained in the water sample on select living organisms, taking into account interactions between all the elements of the tested system [22]. The research results are presented in toxicity units (TU):…”
Section: Introductionmentioning
confidence: 99%